Fuel Loads and Plant Traits as Community‐Level Predictors of Emergent Properties of Vulnerability and Resilience to a Changing Fire Regime in Black Spruce Forests of Boreal Alaska. Issue 3 (16th March 2022) - Grzesik, E. J.; Hollingsworth, T. N.; Ruess, R. W.; Turetsky, M. R.
Abstract: Black spruce forest communities in boreal Alaska have undergone self‐replacement succession following low‐to‐moderate severity fires for thousands of years. However, recent intensification of interior Alaska's fire regime, particularly deeper burning of the soil organic layer, is leading to shifts to deciduous‐dominated successional pathways, resulting in many socioecological consequences. Both fuel load quantity and quality (or "burnability") influence black spruce plant communities' potential to burn. Even relatively low fuel loads, such as those seen in black spruce forest understory, can be highly influential drivers of fire behavior due to their high flammability. Additionally, black spruce community self‐replacement following fire can be largely attributed to the suite of functional and life history traits possessed by the species dominating these communities. We used fuel load (quantity and quality) and amount of within‐population plant trait variation (coefficient of variation; CV) as community‐level emergent properties to investigate black spruce forest vulnerability and resilience to a changing fire regime across the landscape. Our burn severity potential index (BSPI), calculated from fuel load quantity and quality measurements, indicates that drier, higher elevation stands with thicker active layers were the most vulnerable to fire‐induced vegetation shifts under a changing fire regime. Forest resilience to fire‐induced vegetation shift, represented by higher CV, was negatively associated with BSPI and greatest in ecoregions dominated by lowland black spruce forests. Together, these analyses provide critical information for determining the likelihood of stand‐replacing shifts in dominant vegetation following fire and for implementing appropriate ecosystem management practices. Plain Language Summary: As larger and more severe wildfires occur more often, it is becoming increasingly important to understand the ecological effects of fire and to predict how landscapes may change in the future. To investigate properties of black spruce forest vulnerability and resilience to fire‐induced vegetation changes in interior Alaska, we quantified burn severity potential index and plant trait variation for 28 sites using site‐level measurements of fuel load (organic biomass) and plant traits, respectively. We assessed which black spruce forests, in terms of their location across the landscape, are likely the most vulnerable versus the most resilient to severe burning. We found that two types of black spruce forest plant communities (dry nonacidic upland black spruce and dry acidic upland black spruce lichen woodlands) are most vulnerable to experiencing postfire vegetation shifts and, notably, ∼27% of the landscape in interior Alaska is covered by these forest types. Although more research is necessary to verify that plant trait variation is a broadly useful measure of site resilience to fire, these findings will influence future management practices across interior Alaska's landscapes to minimize the loss of social and ecological values that black spruce forests provide. Key Points: Burn severity potential index was significantly related to burn severity, validating it as an indicator of site vulnerability Dry nonacidic upland black spruce and dry acidic upland black spruce lichen woodlands are most vulnerable to fire‐induced vegetation shifts Site‐level coefficient of variation will require further validation as an indicator of forest resilience to severe fire